Considerations for return to exercise following mild-to-moderate COVID-19 in the recreational athlete - Metzl, J. D.; McElheny, K.; Robinson, J. N.; Scott, D. A.; Sutton, K. M.; Toresdahl, B. G. (HSS Journal, 2020)
The COVID-19 pandemic has resulted in significant morbidity and mortality around the world. The spectrum of COVID-19 is broad, from clinical disease requiring intensive medical care to less severe symptoms that are treated with supportive care. The majority of COVID-19 cases fall into the mild-to-moderate category, with symptoms lasting less than 6 weeks. Nevertheless, the morbidity from COVID-19 is significant and can affect multiple body systems, most frequently the cardiac, pulmonary, hematologic, musculoskeletal, and gastrointestinal systems. For patients who wish to return to exercise after mild-to-moderate COVID-19, the wide range of disease expression presents a challenge for clinicians seeking to offer counsel. This literature review on return to activity following mild to moderate COVID-19 in the recreational athlete includes evidence-based considerations and recommendations for clinicians in guiding the safest return to activity.